Gis model of analysis to promote tourism through the use of a web application - Nieto Acevedo, Yuri Vanessa; Romero Villalobos, Oswaldo Alberto; Gallo Ramírez, Kelly Johanna (TECCIENCIA, 2014)
The sustainable development of tourism in little-known towns needs the support of web applications and GIS (Geographic Information System) technology. The aim of this paper is to provide a GIS Model of Analysis integrated into a Web Application called Turichia in order to promote tourism in Chía, a small town in Cundinamarca, Colombia, near Bogotá. The assembly of this web application includes different servers that use ESRI services like Geocoding, Network Analytics, and Web Feature Services and other Geoprocessing operations built in ArcMap for this specific purpose.